SURFACE NANO LEVEL STRUCTURAL MODIFICATION - M.H. SERGEEVA; V.A. KOHANOVSKY (Advanced Engineering Research)
Nano level technologies for wear resistance increase were considered for Different materials: cemented carbides, high speed steels and polymer composites.